Bifidobacterium adolescentis CCFM1447 effectively alleviates osteoporosis by enriching intestinal flora capable of vitamin D conversion - Yu, Xihua; Tian, Gao; Wang, Yi; Li, Liuruolan; Huang, Liming; Zhao, Yurong; Feng, Ling; Zhao, Yuhao; Fang, Haiqin; Lu, Wenwei; Lu, Shourong; Wang, Hongchao (Frontiers in Nutrition, 2025)
IntroductionElderly individuals exhibit heightened susceptibility to osteoporosis, largely attributable to age-related declines in skin, liver, and kidney function. While vitamin D (VD) supplementation is common, its efficacy is often limited, necessitating reliance on pharmaceutical interventions. Research indicates that the intestinal flora significantly influences intestinal VD metabolism, with probiotic supplementation demonstrably impacting circulating VD levels.MethodsWe employed an fecal fermentation model to screen bacterial strains. After introducing these strains into osteoporotic mice, we tested the mice’s serum and skeletal indicators. We then conducted a correlation analysis between the mice’s key intestinal microbiota and serum and skeletal indicators.Results and discussionWe identify Bifidobacterium adolescentis CCFM1447 for its capacity to elevate VD metabolite levels within fermented supernatants. It significantly elevated serum concentrations of 1,25-dihydroxyvitamin D. Furthermore, this intervention improved bone microarchitecture, evidenced by increased trabecular number and bone volume fraction. In addition, the intestinal flora of the osteoporotic mice was disturbed. CCFM1447 intervention increased the relative abundance of beneficial bacteria such as Adlercreutzia equolifaciens, Akkermansia muciniphila and Pediococcus acidilactici. And it is enriched with a part of strains that have the ability to transform VD such as Enterococcus faecalis and Pediococcus acidilactici. The above results suggest that B. adolescentis CCFM1447 may alleviate retinoic acid-induced osteoporosis symptoms by modulating the intestinal flora and increasing the level of active vitamin D.